Trade Group Anatomy Structure and Usage of Nyatoh Wood in The Genus of Palaquium - Kustin Bintani Meiganati; Widya Gumilar Yuldareza Harta; Ina Lidiawati; Kridianto (JURNAL SAINS NATURAL, 2023)
Based on the classification of trade timber species based on the Decree of the Ministry of Forestry No. 163 of 2003, wood species originating from the genera Palaquium, Payena, and Ganua/Madhuca are categorized as Nyatoh wood. The three genera most commonly found in the Indonesian timber trade are wood from the genus Palaquium. The utilization of wood and its economic value can be determined by looking at the characteristics of its anatomical structure. Therefore, it is necessary to observe the anatomical structure of the genus Palaquium wood. Observation of the anatomical structure of wood using the book "Microscopic Characteristics for Identification of Broadleaf Wood" by the Committee of the International Association of Wood Anatomists showed that Nyatoh wood has large fiber sizes with thin walls. In addition, there are prismatic crystals in the parenchyma canals. The prismatic crystal is a latex known as gutta-percha, which can be processed into a good electrical insulator. Another use is for raw materials for pencil rods and veneer raw materials. In assessing the beauty of wood, Nyatoh wood can go up to the commercial beautiful class I, according to the trading timber group assessment system developed by the Forest Products Research and Development Center.